2012
DOI: 10.1139/t2012-041
|View full text |Cite
|
Sign up to set email alerts
|

Geotechnical characteristics of recycled crushed brick blends for pavement sub-base applications

Abstract: This paper presents the findings of a laboratory investigation on the characterization of recycled crushed brick when blended with recycled concrete aggregate and crushed rock for pavement sub-base applications. The engineering properties of the crushed brick blends were compared with typical state road authority specifications in Australia for pavement sub-base systems to ascertain the potential use of crushed brick blends in these applications. The experimental programme included particle-size distribution, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(46 citation statements)
references
References 31 publications
4
39
0
3
Order By: Relevance
“…Arulrajah et al [8] compared the properties of CDD bricks with the properties of crushed brick blends for the Australian pavement sub-base system. Acchar et al [9] confirmed that approximately 50% of CDD can be incorporated into red ceramics, such as brick and tiles without a decrease in their quality.…”
Section: Introductionmentioning
confidence: 99%
“…Arulrajah et al [8] compared the properties of CDD bricks with the properties of crushed brick blends for the Australian pavement sub-base system. Acchar et al [9] confirmed that approximately 50% of CDD can be incorporated into red ceramics, such as brick and tiles without a decrease in their quality.…”
Section: Introductionmentioning
confidence: 99%
“…The "before and after" compaction grading curves (i.e., degree of breakdown that occurred during compaction) would suggest that a maximum of 50% CB material could be used to maintain an acceptable "after compaction" grading (Arulrajah et al 2012a;Rahman et al 2013).…”
Section: Resultsmentioning
confidence: 99%
“…This includes C&D aggregates such as recycled concrete aggregate (Azam and Cameron, 2013;Arulrajah et al 2013a), crushed brick (Aatheesan et al 2010;Arulrajah 2012a), reclaimed asphalt pavement materials (Puppala et al 2011;Arulrajah et al 2013b). Other waste materials that have generated recent interests in various geotechnical applications include waste rock (Arulrajah et al 2012b), waste glass (Ali et al 2011;Disfani et al 2011;Disfani et al 2012;Imteaz et al 2012;Arulrajah et al 2013c) and fly ash Rahman et al 2011;Horpibulsuk et al 2012;Sukmak et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A 4-day soaked period had a negligible influence on the CBR values of the recycled subbase [7], it was feasible to blend recycled concrete aggregate and crushed clay brick to produce a subbase with a soaked CBR value of at least 30%. Aatheesan et al, found that crushed brick could be safely added to crushed rock (class 3) potentially up to 30% [2], and could be safely added to recycle concrete aggregate and crushed rock blends with percent up to 25% [8]. Arulrajah et al, concluded that crushed brick may have to be blended with other durable aggregates to improve its durability and to enhance its performance in pavement sub-base [9].…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%